INFLUENCE OF LDPE PACKAGING ON POST HARVEST QUALITY OF MANGO FRUITS DURING LOW TEMPERATURE STORAGE - P. P. S GILL,; S. K. JAWANDHA,,; NAVDEEP KAUR,; NAVPREM SINGH,; ANIL SANGWAN, (The Bioscan, 2015)
The present studies were conducted to examine the effect of LDPE (Low density polyethylene) packaging on quality of Dashehari mango fruits under low temperature storage. Physiological mature fruits were subjected to LDPE packaging with different perforation levels (0, 0.05 and 0.1%) and were placed at 12±1oC for 4 weeks. The control fruits were packed in corrugated fiber board boxes. After four weeks of storage, minimum PLW (2.03 %) was registered in non-perforated LDPE packaged fruits while maximum PLW (9.86 %) was recorded in control fruits. This treatment also retained maximum fruits firmness (5.8 lbf) after three weeks of storage. However, maximum soluble solids content (17.20 %) were recorded in LDPE (0.1% perforation) packed fruits after 3 weeks of storage. At the end of storage, fruits kept in non-perforated LDPE packaging resulted in highest (0.41%) juice acidity while control fruits had lowest (0.18%) acidity. Similarly, control fruits developed maximum sensory quality rating of 8.5 till two weeks of storage and then showed declining trend. Maximum β-carotene content (3.32 mg/100g of pulp) was recorded in control fruits at 3rd week of storage. In conclusions, LDPE packaging (0.1 % perforation) of Dashehari mango fruits was effective in maintaining quality characteristics up to three weeks under low temperature storage.